Penerapan Model Pembelajaran Problem Based Learning : Literature Review - Hamdiah Ahmar; Prastawa Budi; Mardiana Ahmad; Ahmad Mushawwir; Zul Khaidir (Jurnal Keperawatan Muhammadiyah, 2020)
The emphasis of midwifery education is the process of educating and enhancing the ability of individuals to become midwives who are able to carry out midwifery practices in a professional manner. To increase student graduation in the competency test, special attention is needed as well as a good learning process so that learning objectives can be achieved. One of the factors that causes the low quality of education is the factor of teaching and learning process (teaching learning). The purpose of conducting a competency test is to protect the community by providing assurance that registered entry level health workers have the required competencies. Problem-based learning model (Problem Based Learning) is a student-centered learning strategy, develops active learning, problem solving skills and field knowledge, and is based on understanding and solving problems. Study this literature through searching scientific publications in the 2017-2020 range using several databases namely Pubmed, Science Direct, and Wiley Online. as many as 7 articles that correspond to the objects discussed in the literature review with inclusion criteria and article search exclusion criteria. Pubmed literature search results N = 99, Science direct N = 67, Wiley N = 23, screening by title N = 14, Screening by Content N = 9. The use of appropriate learning methods can provide better learning outcomes, PBL is easier to apply and requires less preparation time, several techniques for applying problem based learning in the learning process: a) Paper Problem Based Learning, b) Virtual Problem-Based Learning , c) Scripting-based learning combining wearable technology, d) Hybrid Problem-Based Learning